A new genus and two new species of Orthotylinae (Hemiptera: Heteroptera: Miridae) from central Australia - Namyatova, Anna A.; Elias, Michael; Cassis, Gerasimos (Zootaxa, 2011)
Witchelinamiris gen.nov. and W. mchughi sp. nov. and W. viridimaculatus sp. nov. are described as new to science. Digital images, scanning electron micrographs, and illustrations of the male genitalia are provided for both species, and illustrations of the female genitalia are provided for W. viridimaculatus. Information on collection methods and host plants is included.